2015
DOI: 10.1111/ecc.12425
|View full text |Cite
|
Sign up to set email alerts
|

Preferences of lung cancer patients for treatment and decision-making: a systematic literature review

Abstract: The consideration of patient preferences in decision-making has become more important, especially for life-threatening diseases such as lung cancer. This paper aims to identify the preferences of lung cancer patients with regard to their treatment and involvement in the decision-making process. We conducted a systematic literature review from 12 electronic databases and included studies published between 2000 and 2012. A total of 20 studies were included in this review. These revealed that lung cancer patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
38
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 38 publications
(101 reference statements)
1
38
0
Order By: Relevance
“… 4 9 However, we performed a systematic literature review which showed that, in general, patients do not wish to decide on their therapy personally and would prefer their physician to make the decision. 10 , 11 Here, a conflict can occur, because the therapy that is provided to patients should be adjusted to meet their preferences regarding HRQoL and adverse effects. Previous studies on other diseases have shown that satisfaction with therapy can have a significant effect on disease outcomes and further treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“… 4 9 However, we performed a systematic literature review which showed that, in general, patients do not wish to decide on their therapy personally and would prefer their physician to make the decision. 10 , 11 Here, a conflict can occur, because the therapy that is provided to patients should be adjusted to meet their preferences regarding HRQoL and adverse effects. Previous studies on other diseases have shown that satisfaction with therapy can have a significant effect on disease outcomes and further treatment decisions.…”
Section: Introductionmentioning
confidence: 99%
“…2013Sadique [30]2011Women’s preferences regarding optionsfor management of atypical, borderlineor low-grade cervical cytological abnormalities: a review of the evidence“To identify empirical studies evaluating women’s preferences regarding alternative management pathways & to compare the impact of alternative elicitation methods on results.”March 2009Schatz [31]2015Systematic review of patients’ & parents’ preferences for ADHD treatment options& processes of care“To synthesize reports across existing DCE, BWS, TTO, & SGI studies to assess which aspects of ADHD treatment are most studied as well as most preferred & influential in treatment decisions.”Oct. 2014Schmidt [32]2016Preferences of lung cancer patients for treatment & decision-making: asystematic literature review“To identify the preferences of lung cancer patients with regard to their treatment & involvement in the decision-making process.”Sept. 2012Showalter [33]2015Factors that influence patient preferences for prostate cancer management options:a systematic review“We performed a systematic review to evaluate evidence regarding factors that influence patient preferences for management options for localized prostate cancer.”April 2014Stewart [34]2016Preference for pharmaceuticalformulation & treatment processattributes“To examine studies on preferences for pharmaceutical treatment process attributes, focusing on research in diabetes, oncology, osteoporosis, & autoimmune disorders.”Oct.…”
Section: Resultsmentioning
confidence: 99%
“…Desire for substantial engagement in decision-making has previously been demonstrated among breast cancer patients [46,47]. Furthermore, Schmidt and colleagues [2016], observed that preferences were not homogenous among lung cancer patients, and some subjects seemed to prefer a passive rather than an active role in decision-making [48]. The present study has shown a greater preference in patients for being involved in the decision-making process rather than choosing their own treatment after consulting the doctor, as already reported in the literature for colorectal cancer [49].…”
Section: Discussionmentioning
confidence: 99%